Optimalisasi dalam Penentuan Keputusan Level Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) Menerapkan Metode Preference Selection Index - Rohan Kristini Purba; Dendy Frans Gunawan Hutagalung; Ebenezer Maston Sinaga; Agustina Sidabutar; Mesran Mesran (Journal of Information System Research (JOSH), 2022)
The Covid-19 pandemic is a disaster for the entire world, even affecting all aspects of human life, both in terms of economy, social and culture. Therefore, the government enacted a regulation called Large-Scale Social Restrictions (PSBB) to stop the spread of COVID-19. In this case, the government makes a policy to change the Large-Scale Social Restrictions (PSBB) into the Enforcement of Community Activity Restrictions (PPKM) where the PSBB Restrictions are stricter than the Enforcement of Community Activity Restrictions (PPKM). Because the absence of a system makes it difficult for the government and requires a long time in determining the level of implementation of restrictions on community activities (PPKM). In order to assist in determining the level of PPKM, a decision support system is needed. The Preference Selection Index (PSI) method is a method used in a decision support system using simple steps in problem solving. The results of the research obtained that the highest rank is A7 with a value of 0.767 as level 1. By using the range on the PPKM level so that level 1 is Sibolga. Level 2 does not exist in the above alternative. Level 3 is terrain, Binjai, Pematang Siantar, Tebing Tinggi, Gunung Sitoli, Padang Sidimpuan, Tanjung Balai, Samosir and Kisaran and level 4 is not in the alternatives.